2012
DOI: 10.1136/bjsports-2012-091300
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute anterior shoulder dislocation

Abstract: Shoulder dislocation is the most common large joint dislocation in the body. Recent advances in radiological imaging and shoulder surgery have shown the potential dangers of traditional reduction techniques such as the Kocher's and the Hippocratic methods, which are still advocated by many textbooks. Many non-specialists continue to use these techniques, unaware of their potential risks. This article reviews the clinical and radiographic presentation of dislocation; some common reduction techniques; their risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 64 publications
0
57
0
2
Order By: Relevance
“…In international literature numerous techniques have been described but there is a conflict about which is the more effective one [13]. Techniques of reduction of dislocated shoulder are classified in two categories: leverage (Kocher, Milchs, Cunningham technique) and traction (Hippocrates, Stimson, Eskimo, Spaso, Scapular manipulation technique, Fares method) [14]. All these techniques have advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…In international literature numerous techniques have been described but there is a conflict about which is the more effective one [13]. Techniques of reduction of dislocated shoulder are classified in two categories: leverage (Kocher, Milchs, Cunningham technique) and traction (Hippocrates, Stimson, Eskimo, Spaso, Scapular manipulation technique, Fares method) [14]. All these techniques have advantages and disadvantages.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple methods for reduction of shoulder dislocation have been described (Cunningham, 2005), however it has been suggested that the optimal technique should be quick, effective, simple to perform and should require minimal force, analgesia and assistance (Dala-Ali et al, 2014).…”
Section: Case Progression and Discussionmentioning
confidence: 99%
“…First, sideline clinicians should be expert at relocating shoulders with appropriate precautions 2. In the office consultation, factors providing high risk of recurrent instability include: age of 20 years, bony pathology such as large glenoid fractures or Hill-Sachs lesions, generalised ligamentous laxity, and participation in high-risk sport such as collision sports.…”
Section: What Should Clinicians Do?mentioning
confidence: 99%